Functional brain asymmetry and cognitive functions in elite wrestlers - Korobeynikov, G.; Korobeinikova, L. (International Journal of Wrestling Science, 2014)
Functional brain asymmetry is a one of the fundamental genetic characteristics in human. The peculiarities of functional brain asymmetry and cognitive functions in elite wrestlers were studied. A total 29 elite wrestlers (18-25 yrs), members of the Ukrainian National Team in Greco-Roman wrestling were examined. The perception and processing of visual information in athletes with different brain asymmetry were studied. The function of brain asymmetry in elite wrestlers is characterized of a high level of dependence on the external environment. The presence of symmetry is correlated with a high level of independence from the external environment providing an efficacious level of cognitive functions in wrestlers. We conclude that wrestlers with brain symmetry have better possibilities to manifest cognitive functions: operative thinking, perception and information processing in comparison to wrestlers with functional asymmetry of brain.